The biochemical analysis of mucus and mucins in respiratory diseases with a focus on tuberculosis - Mofokeng, Henrietta Refiloe (Department of Surgery, 2017)
Respiratory diseases are a major cause of death in South Africa, with TB being one of the major respiratory illnesses. The respiratory tract is lined by a layer of mucus which protects the airways and lungs against injury by foreign agents. The main constituents of this layer of mucus are mucins. MUC5AC and MUC5B are the predominant respiratory tract mucins. However, little is known of the association between respiratory mucins and TB. This study aimed at describing the types and role of respiratory mucins in TB. Fifty six sputum samples, 17 tracheal aspirates and 95 bronchoalveolar lavages (BALs) were collected in 6M guanidinium hydrochloride and inhibitors. The airway mucus was divided into TB and non-TB groups. Mucins were reduced and alkylated with DTT and iodoacetamide and purified by density gradient ultracentrifugation in caesium chloride. Identification of MUC5AC, MUC5B, MUC2 and MUC7 were determined by western blotting and confirmed by immunohistochemistry. Western blot data proved the dominance of MUC5AC and MUC5B mucins in airway mucus. In comparison to the non-TB group, a higher secretion of MUC5AC than MUC5B in patients with TB was observed. MUC5AC also showed distinct behavioural characteristics in its fractionation in a caesium gradient compared to MUC5B. The presence of MUC5AC and MUC5B in different fractions suggests varying glycosylation of the mucin. Varying populations of MUC5B were observed in sputa with 3 new glycoforms shown in TB. A small group of TB patients had MUC7 in the sputa (and not in the lavage) and there were varying amounts of MUC2 in some TB samples and non-TB mucus. At tissue level, MUC5B was found to be the main secreted gel-forming mucin. MUC5B and MUC7 were found to play a role in the protection again infection by Mycobacterium tuberculosis in tuberculous granulomas. Using proteomics it was demonstrated that respiratory mucus protein expression differs in, tracheal aspirates, BALs and sputa. Although inter-individual variations were observed in all samples, similar proteins were expressed in relation to the functioning of the lung. O-glycan analysis showed that the majority of the O-glycans detected were sialylated and that core 3 and 4 O-glycan structures diminished in the presence of HIV.